2022
DOI: 10.1111/ijfs.15767
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in quality formation and characterisation of tea products: a review

Abstract: Summary Tea is one of the biggest categories of modern non‐alcoholic beverages with health benefits. Through different processes, tea products are divided into six main types: green tea, yellow tea, white tea, oolong tea, black tea and dark tea. Metabolomics is helpful for the comprehensive, accurate and rapid determination of tea metabolites in different types of tea products and tea processing materials. It has been widely applied in studying the relationship of tea metabolites and its quality. Therefore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…After withering, the tea leaves entered fermentation, which was an important link to the formation of key odor characteristics of Wuyi rock tea ( Liu et al, 2023 ). The fermentation process of Wuyi rock tea was special and complex, and the fermentation of high-quality Wuyi rock tea required 5 to 6 operations, and during each fermentation process, the transformation of substances in the tea leaves constantly intensified, which finally resulted in the formation of a special flavor of Wuyi rock tea ( Wang et al, 2020 ; Cai et al, 2022 ). During the fermentation process, the enzyme activity in tea leaves increased dramatically, and the change in enzyme activity promoted the transformation of substances in tea leaves, which was conducive to the accumulation of inclusions in tea leaves ( Zhao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…After withering, the tea leaves entered fermentation, which was an important link to the formation of key odor characteristics of Wuyi rock tea ( Liu et al, 2023 ). The fermentation process of Wuyi rock tea was special and complex, and the fermentation of high-quality Wuyi rock tea required 5 to 6 operations, and during each fermentation process, the transformation of substances in the tea leaves constantly intensified, which finally resulted in the formation of a special flavor of Wuyi rock tea ( Wang et al, 2020 ; Cai et al, 2022 ). During the fermentation process, the enzyme activity in tea leaves increased dramatically, and the change in enzyme activity promoted the transformation of substances in tea leaves, which was conducive to the accumulation of inclusions in tea leaves ( Zhao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is an effective tool for explaining the effects of metabolites in tea fermented by microorganisms ( Cai et al, 2022 ). Metabolomics analysis showed that certain microorganisms have important effects on the transformation of metabolites and flavor formation during pile-fermentation ( Shi et al, 2021 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…From 2000 to the present, metabolomics has attracted more and more attention and been widely applied in tea industry involving cultivation, processing, as well as classification of cultivars, grades, and origins (Cai et al., 2022). Although several articles have reviewed the applications of metabolomics in tea studies, systematic and comprehensive reviews are still lacking (Cai et al., 2022; Farag et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…From 2000 to the present, metabolomics has attracted more and more attention and been widely applied in tea industry involving cultivation, processing, as well as classification of cultivars, grades, and origins (Cai et al., 2022). Although several articles have reviewed the applications of metabolomics in tea studies, systematic and comprehensive reviews are still lacking (Cai et al., 2022; Farag et al., 2023). Hence, we carefully analyzed the published tea metabolomics articles and summarized the achievements of tea metabolomics focusing on tea metabolite variation during tea plant growth under different environmental conditions and during different processing stages, as well as metabolite differences in tea samples with different cultivars, grades, geographical origins, and tea types over the past two decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation